2015
DOI: 10.1007/s10943-014-9995-z
|View full text |Cite
|
Sign up to set email alerts
|

Religious, Ethical and Legal Considerations in End-of-Life Issues: Fundamental Requisites for Medical Decision Making

Abstract: Religion and spirituality have always played a major and intervening role in a person's life and health matters. With the influential development of patient autonomy and the right to self-determination, a patient's religious affiliation constitutes a key component in medical decision making. This is particularly pertinent in issues involving end-of-life decisions such as withdrawing and withholding treatment, medical futility, nutritional feeding and do-not-resuscitate orders. These issues affect not only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…The data demonstrate that religious teachings about end-of-life care may be influential in shaping patients' and families' orientation and preferences to medical treatment, which has also been previously reported 11. As Jahn Kassim and Alias16, p. 7 state, ‘religion and religious traditions serve two primary functions, namely the provision of a set of core beliefs about life events and the establishment of an ethical foundation for clinical decision making’. As demonstrated in the data, families used religion as a value system to inform their decision-making or to affirm their choices about medical treatment.…”
Section: Discussionsupporting
confidence: 66%
“…The data demonstrate that religious teachings about end-of-life care may be influential in shaping patients' and families' orientation and preferences to medical treatment, which has also been previously reported 11. As Jahn Kassim and Alias16, p. 7 state, ‘religion and religious traditions serve two primary functions, namely the provision of a set of core beliefs about life events and the establishment of an ethical foundation for clinical decision making’. As demonstrated in the data, families used religion as a value system to inform their decision-making or to affirm their choices about medical treatment.…”
Section: Discussionsupporting
confidence: 66%
“…[8] Consensus on policy or law could improve attitudes regarding DNR orders and encourage clinicians to make medical decisions in favor of patients themselves. [61,62]…”
Section: Discussionmentioning
confidence: 99%
“…Our research was retrospective; thus, patients’ psychological states and the reasons for deciding for or against a DNR order cannot be known. Although studies from other countries have found that religion is an important factor influencing DNR orders, [6,61] medical records in China have no such information. It may be necessary to perform a prospective study about the impact of religion on DNR orders in China.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they do support administrating palliative care and spiritual support to a dying patient (Tomkins et al, ). In general, religious laws are highly influential in EOL decisions: stopping treatment or refusing it when it is ineffective, decisions about nutritional support, and advance directives by a patient who is not interested in life‐prolonging treatment (Jahn Kassim & Alias, ).…”
Section: Introductionmentioning
confidence: 99%